Estimation of geophysical and physical and mechanical properties on the example of quaternary soils of Sergiev Posad district - V. V. Romanov; D. S. Daev; L. E. Chesalov; A. I. Poserenin (Известия высших учебных заведений: Геология и разведка, 2018)
The Sergiev Posad polygon of the MGRI-RSGPU is located on the watershed of the Pazha and Torgosha rivers located on the southern slope of the Klinsky-Dmitrovsky ridge; geologically, the upper part of its section is composed of clay soils of Quaternary and Cretaceous age. The paper gives an analysis of the values of seismic, electrical and physical and mechanical properties of soils, as well as resistivity of water sources and reservoirs. Main methods of near-surface geophysics allow obtaining this information. The performed methods made it possible to specify the geological structure of the first 15 meters of the section, to refine the hydrogeological conditions of the test site, to determine the properties of the grounds as bases for buildings and structures. Also, the effect of the radioactive substance oonthe state of the underlying soils has been established by means of a specially prepared soil radiometer plate .